Prevention of Incisional Hernias with Biological Mesh: A Systematic Review of the Literature - Muysoms, Filip E.; Jairam, An; López-Cano, Manuel; Śmietański, Maciej; Woeste, Guido; Kyle-Leinhase, Iris; Antoniou, Stavros A.; Köckerling, Ferdinand; , BioMesh Study Group; Köckerling, Ferdinand; Antoniou, Stavros; Fortelny, René; et al. (Frontiers in Surgery, 2016)
Background Prophylactic mesh-augmented reinforcement during closure of abdominal wall incisions has been proposed in patients with increased risk for development of incisional hernias (IHs). As part of the BioMesh consensus project, a systematic literature review has been performed to detect those studies where MAR was performed with a non-permanent absorbable mesh (biological or biosynthetic). Methods A computerized search was performed within 12 databases (Embase, Medline, Web-of-Science, Scopus, Cochrane, CINAHL, Pubmed publisher, Lilacs, Scielo, ScienceDirect, ProQuest, Google Scholar) with appropriate search terms. Qualitative evaluation was performed using the MINORS score for cohort studies and the Jadad score for randomized clinical trials (RCTs). Results For midline laparotomy incisions and stoma reversal wounds, two RCTs, two case–control studies, and two case series were identified. The studies were very heterogeneous in terms of mesh configuration (cross linked versus non-cross linked), mesh position (intraperitoneal versus retro-muscular versus onlay), surgical indication (gastric bypass versus aortic aneurysm), outcome results (effective versus non-effective). After qualitative assessment, we have to conclude that the level of evidence on the efficacy and safety of biological meshes for prevention of IHs is very low. No comparative studies were found comparing biological mesh with synthetic non-absorbable meshes for the prevention of IHs. Conclusion There is no evidence supporting the use of non-permanent absorbable mesh (biological or biosynthetic) for prevention of IHs when closing a laparotomy in high-risk patients or in stoma reversal wounds. There is no evidence that a non-permanent absorbable mesh should be preferred to synthetic non-absorbable mesh, both in clean or clean-contaminated surgery.